Effect of Boiling Time on the Change of Moisture Content, Color Analysis and Granule’s Shape of Breadnut (Artocarpus camansi) Flour - Diandra, Azzahra Putri; Zain, Alya Yuniza Maharani; Hanina, Khansa; Apriliani, Vania Rahmawati; Azis, Lukman (Universitas Al Azhar Indonesia, 2023)
Breadnut is a local product with short shelf life that not optimally process and utilized in Indonesia. Breadnut is easily browning due to enzymatic activity. Meanwhile, breadnut potentially become alternative product due to the nutritional value mainly carbohydrate. The aim of this study evaluated the effect of boiling time on the change of moisture content, color analysis and granule’s shape of breadnut flour. Moisture content was analysis using gravimetric method then color analysis and shape of granule were using color meter and digital microscope, respectively. Data was expressed of mean±SD while statistically analysis using ANOVA with Duncan’s test to determine the significant difference (p<0.05). The results of this study showed that the moisture content, L and b* value of breadnut flour with boiling time of 10 and 15 minutes showed not significant difference (p>0.05). In addition, a* value not significant differ (p>0.05) for the breadnut with boiling time of 0 and 5 minutes. The granule’s shape of breadnut under microspore was visualized that boiling time change the size and shape of the granule due to heating and swelling. In conclusion, boiling time was changing the moisture content, color analysis and granule’s shape of breadnut flour.